Molecular and clinical analysis of Ellis-van Creveld syndrome in the United Arab Emirates - Ali, Bassam R (BioMed Central, 2010)
BACKGROUND: Ellis-van Creveld (EvC) syndrome is an autosomal recessive chondrodysplastic condition with clinical manifestations that include short-limbs and ribs, postaxial polydactyly and dysplastic nails and teeth. In about two thirds of patients, mutations in either EVC or EVC2 genes have been found to be the underlying cause. METHODS: In this paper, we describe the molecular (DNA sequencing) and clinical analysis of six children diagnosed with EvC from four different families from the United Arab Emirates (UAE). RESULTS: All the children had the common clinical and radiological features of this syndrome. However, DNA sequence analysis of the genes shown to be involved (EVC and EVC2) revealed a novel splice site mutation (c.2047-1G>T) in intron 13 of EVC2 gene in one family. In addition, we confirm previous mutational analyses that showed a truncating mutation in exon 13 of EVC gene (c.1813C>T; p.Q605X) in the second family and a single nucleotide deletion (c.981delG; p.K327fs) in exon 8 of EVC2 gene in the third family. No mutations in the exons, splice sites or the promoter regions of either gene have been found in the index case of the fourth family who exhibited "EvC-like" features. CONCLUSIONS: Given the small population size of UAE, our data illustrates further the molecular heterogeneity observed in EvC patients and excludes the possibility of a common founder effect for this condition in the UAE reflecting the current ethnic diversity of the country.